2023
DOI: 10.36469/jheor.2020.13348
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Vaso-Occlusive Crises and Opioid Prescriptions Among Patients with Sickle Cell Disease: A Retrospective Claims-Based Study

Abstract: Background/Objectives: Among sickle cell disease (SCD) patients, vaso-occlusive crises (VOCs) are recurrent and unpredictable attacks of acute pain. These pain crises are often treated with analgesics, including opioids, which have been associated with misuse and overdose. The aim of this study was to examine the association between VOC events and opioid use and assess the association between opioid prescriptions and health care resource utilization among SCD patients. Methods: This was a retrospective cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 51 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…Numerous peer‐reviewed studies that analyzed public or private claims databases have required either 1 inpatient claim with a diagnosis code for SCD or ≥2 outpatient claims with a diagnosis code for SCD on separate days to identify cases of SCD 2,3,25–45 . One of these studies excluded individuals who also had a claim with a diagnosis code for sickle cell trait, 40 citing a Wisconsin study that reported that individuals who had diagnosis codes for both SCD (282.60) and sickle cell trait were confirmed to have trait 8 …”
Section: Algorithms For Detection Of Scdmentioning
confidence: 99%
“…Numerous peer‐reviewed studies that analyzed public or private claims databases have required either 1 inpatient claim with a diagnosis code for SCD or ≥2 outpatient claims with a diagnosis code for SCD on separate days to identify cases of SCD 2,3,25–45 . One of these studies excluded individuals who also had a claim with a diagnosis code for sickle cell trait, 40 citing a Wisconsin study that reported that individuals who had diagnosis codes for both SCD (282.60) and sickle cell trait were confirmed to have trait 8 …”
Section: Algorithms For Detection Of Scdmentioning
confidence: 99%
“…This finding was reflected in two recent studies: one that reported that 240 million opioid prescriptions were dispensed in the USA in 2015 (equivalent to almost one prescription for every adult in the general population) 21 and another SCD-based study in the USA that identified that each VOC was associated with an increased use of opioids. 22 The US campaign to identify pain as the fifth vital sign has been a key driver in compelling providers to prescribe opioids for pain. 16 It is important to note that while opioids (both intravenous and oral) remain a valid treatment option for patients with SCD, 23 their availability is country dependent, and particularly limited in many countries across Africa and the Middle East.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, as morphine is metabolized by liver glucuronidation, dosage adjustment should be considered in patients with liver dysfunction [ 8 ]. One study concluded that with each VOC event, there is an expected 9.5% increase in opioid prescription use [ 4 ]. Long-term opioid use is associated with the risk of abuse potential, leading to physical tolerance, physical and psychological dependence, addiction, and possible opioid hyperalgesia [ 5 ].…”
Section: Reviewmentioning
confidence: 99%
“…Acute painful crisis (APC) is a consequence of microcirculation occlusion by sickle hemoglobin-containing red blood cells (RBCs), leading to ischemia, inflammation, and subsequent tissue damage [ 3 ]. These pain crises are often recurrent and unpredictable forms of acute pain [ 4 ]. The Cooperative Study of Sickle Cell Disease defines an acute pain crisis as an episode of pain in the extremities, back, abdomen, or head lasting more than two hours that leads to a clinic visit that cannot be explained by any etiology other than SCD.…”
Section: Introductionmentioning
confidence: 99%